Wisconsin uprising : labor fights back - Yates, Michael, 1946-; McChesney, Robert Waterman, 1952- (Monthly Review Press, 2010)
In early 2011, the nation was stunned to watch Wisconsin's state capitol in Madison come under sudden and unexpected occupation by union members and their allies. The protests to defend collective bargaining rights were militant and practically unheard of in this era of declining union power. Nearly forty years of neoliberalism and the most severe economic crisis since the Great Depression have battered the labor movement, and workers have been largely complacent in the face of stagnant wages, slashed benefits and services, widening unemployment, and growing inequality. That is, until now.